Adherence to disease-specific drug treatment among patients with pulmonary arterial hypertension or chronic thromboembolic pulmonary hypertension. Issue 4 (7th December 2020) - Kjellström, Barbro; Sandqvist, Anna; Hjalmarsson, Clara; Nisell, Magnus; Näsman, Per; Ivarsson, Bodil
Background: Pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) require lifelong treatment. The aim of the present study was to investigate adherence to disease-specific treatment in patients with PAH or CTEPH. Methods: The study comprised an adult population diagnosed with PAH (n=384) or CTEPH (n=187) alive in 2016–2017. The study utilised three registries: the Swedish PAH registry, the National Board of Health and Welfare, and Statistics Sweden. Withdrawals from pharmacies of disease-specific oral treatments were studied. Adherence was assessed as: 1) Number of days covered defined as the difference between the total number of daily dosages dispensed and the total number of days covered; and 2) Manual assessment by two persons that independently reviewed each patient's prescription fill history to detect anomalies or patterns of deteriorating or improving adherence over time. Results: The mean age was 61±16 years, 61% were female and mean time since diagnosis was 4.6 years. Adherence was 62% using the Number of days covered method and 66% by the Manual assessment method. Drug-specific adherence varied from 91% for riociguat to 60% for sildenafil. Good adherence was associated with shorter time since diagnosis in patients with PAH and with lower number of concomitant other chronic treatments in patients with CTEPH. Age, sex, socioeconomic status or number of pulmonary hypertension (PH) treatments were not associated with adherence. Conclusion: Adherence to oral disease-specific treatment was 60–66% and associated with time since diagnosis and number of concomitant chronic treatments. Sex, age or socioeconomic factors did not affect adherence. Adherence to oral ERA and/or PDE-5i/SGC treatment is associated with time since diagnosis, while sex, gender, age and socioeconomic factors do not affect adherence in patients with PAH or CTEPH https://bit.ly/354NAOQ